Dielectric microwave absorbing material processed by impregnation of carbon fiber fabric with polyaniline - Folgueras, Luiza De Castro (2007)
It is a known fact that the adequate combination of components and experimental conditions may produce materials with specific requirements. This study presents the effect of carbon fiber fabric impregnation with polyaniline conducting polymer aiming at the radar absorbing material processing. The experiments consider the sample preparation with one and two impregnations. The prepared samples were evaluated by reflectivity measurements, in the frequency range of 8-12 GHz and scanning electron microscopy analyses. The correlation of the results shows that the quantity of impregnated material influences the performance of the processed microwave absorber. This study shows that the proposed experimental route provides flexible absorbers with absorption values of the incident radiation close to 87%.